2021
DOI: 10.1186/s12889-021-10927-1
|View full text |Cite
|
Sign up to set email alerts
|

Worry and mental health in the Covid-19 pandemic: vulnerability factors in the general Norwegian population

Abstract: Background There is an urgent need for knowledge about the mental health consequences of the ongoing pandemic. The aim of this study was to identify vulnerability factors for psychological distress and reduced life satisfaction in the general population. Furthermore, we aimed to assess the role of COVID-related worries for psychological distress and life satisfaction. Methods A presumed representative sample for the Norwegian population (n = 1041, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 32 publications
8
78
1
1
Order By: Relevance
“…In total, 39.9% (N = 1,041) completed the survey, 55.8% (N = 1,457) did not respond, 2.7% (N = 71) started the survey but did not complete it, 1.6% (N = 41) clicked on the link to participate but did not confirm their agreement to the terms of the study, and 0.1% (N = 2) withdrew from the study. Our study participants did not significantly differ from non-responders in gender or education, but the sample was highly skewed toward older age, with a mean age of 54.1 in responders and 43.3 in non-responders (Blix et al, 2021).…”
Section: Participantsmentioning
confidence: 67%
See 2 more Smart Citations
“…In total, 39.9% (N = 1,041) completed the survey, 55.8% (N = 1,457) did not respond, 2.7% (N = 71) started the survey but did not complete it, 1.6% (N = 41) clicked on the link to participate but did not confirm their agreement to the terms of the study, and 0.1% (N = 2) withdrew from the study. Our study participants did not significantly differ from non-responders in gender or education, but the sample was highly skewed toward older age, with a mean age of 54.1 in responders and 43.3 in non-responders (Blix et al, 2021).…”
Section: Participantsmentioning
confidence: 67%
“…Pandemic-related worries the participants were asked to indicate their level of worry on a scale from 1 (not worried) to 7 (very worried) for 12 questions about COVID-related worries adapted from the COSMO study (Betsch et al, 2020). In a previous paper (Blix et al, 2021), we conducted a confirmatory factor analysis, resulting in support for six worry items that are believed to represent an underlying worry factor. We asked participants how much they worried about "losing someone I love, " "becoming seriously ill from the virus, " "infecting others, " 2 www.europeansocialsurvey.org/data/country.html?c=norway "the health system being overloaded, " "not being able to visit people who depend on me, " and "a new outbreak of COVID-19."…”
Section: Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…By the end of May 2021, the coronavirus disease 2019 (COVID- 19) pandemic afflicted more than 170 million people worldwide (1). The outbreak of COVID-19 has caused various mental health problems in the public and vulnerable populations, including healthcare workers, elderly, pregnant women, and children (2)(3)(4)(5)(6)(7)(8). Although children have a lower infection rate and relatively mild clinical symptoms, those with COVID-19 infection are considered more susceptible to mental health problems compared with unaffected children (9).…”
Section: Introductionmentioning
confidence: 99%
“…Population samples of IPGs have reported high levels of psychiatric comorbidity with more than one third meet criteria for an anxiety disorder ( Lorains et al, 2011 ). A Norwegian study during the pandemic showed that those with prior mental health problems, financial problems and those living alone were also more likely to experience higher levels of pandemic related worries ( Blix et al, 2021 ). The effect of the pandemic is diverse as noted but might have an amplifying affect on previous risk factors such a symptoms of anxiety.…”
Section: Discussionmentioning
confidence: 99%